Fusaric acid induces oxidative stress and apoptosis in human cancerous oesophageal SNO cells. (February 2017) - Devnarain, Nikita; Tiloke, Charlette; Nagiah, Savania; Chuturgoon, Anil A.
Abstract: Oesophageal cancer (OC) is a global problem incrementally incident among black South African males. The high incidence of OC may be due to the consumption of corn as a staple, often contaminated with mycotoxins. Fusaric acid (FA), a neglected mycotoxin, is known to disrupt mitochondrial energy metabolism, chelates divalent metal cations and induces cell death in plants. This study investigated FA-induced cytotoxicity and apoptotic induction in the SNO OC cell line. Cells were treated with FA (IC50 = 78.81 μg/mL; 24 h; MTT assay) and assayed for oxidative stress and membrane damage (TBARS, LDH cytotoxicity and glutathione), apoptotic induction (ATP levels, caspase-8, -9, -3/7 activities) (Luminometry), single strand DNA and nuclear fragmentation (Comet and Hoechst assay). Additionally, relative expression of pro- and anti-apoptotic proteins were determined (Western Blotting). Significant antioxidant depletion was consistent with a concomitant increase in ROS-induced lipid peroxidation and extracellular LDH levels. FA induced apoptosis by significantly increasing Bax expression and caspase-8, -9 and -3/7 activities whilst decreasing ATP levels and Bcl-2 expression. Further, FA significantly increased comet tail lengths, PARP-1 expression and late stage apoptotic body formation in SNO cells. This study shows that FA is cytotoxic and induces increased apoptosis in SNO cells. Graphical abstract: Highlights: Fusaric acid (FA) reduced metabolic activity and cell viability in SNO cells. FA increased ROS-induced lipid peroxidation with a concomitant decrease in glutathione. FA decreased ATP levels and increased LDH leakage from SNO cells. FA induced apoptosis by increasing caspase-3/7, -8 and -9 activities and DNA damage.